How do culture media influence in vitro perivascular cell behavior?. (6th August 2015) - Huber, Birgit; Volz, Ann‐Cathrin; Kluger, Petra Juliane
Abstract: Perivascular cells are multilineage cells located around the vessel wall and important for wall stabilization. In this study, we evaluated a stem cell media and a perivascular cell‐specific media for the culture of primary perivascular cells regarding their cell morphology, doubling time, stem cell properties, and expression of cell type‐specific markers. When the two cell culture media were compared to each other, perivascular cells cultured in the stem cell medium had a more elongated morphology and a faster doubling rate and cells cultured in the pericyte medium had a more typical morphology, with several filopodia, and a slower doubling rate. To evaluate stem cell properties, perivascular cells, CD146 − cells, and mesenchymal stem cells (MSCs) were differentiated into the adipogenic, osteogenic, and chondrogenic lineages. It was seen that perivascular cells, as well as CD146 − cells and MSCs, cultured in stem cell medium showed greater differentiation than cells cultured in pericyte‐specific medium. The expression of pericyte‐specific markers CD146, neural/glial antigen 2 (NG2), platelet‐derived growth factor receptor‐β (PDGFR‐β), myosin, and α‐smooth muscle actin (α‐SMA) could be found in both pericyte cultures, as well as to varying amounts in CD146 − cells, MSCs, and endothelial cells. The here presented work shows that perivascular cells can adapt to their in vitro environment and cell culture conditions influence cell functionality, such as doubling rate or differentiation behavior. Pericyte‐specific markers were shown to be expressed also from cells other than perivascular cells. We can further conclude that CD146 + perivascular cells are inhomogeneous cell population probably containing stem cell subpopulations, which are located perivascular around capillaries.